Religiosity, Smoking and Other Risky Behaviors - Monica Roman; Klaus F. Zimmermann; Aurelian-Petruș Plopeanu (Global Labor Organization (GLO), 2022)
While under communism the identity-providing religion was suppressed, religiosity is strong today even among the youth in post-communist countries. This provides an appropriate background to investigate how external and internal religiosity relates to risky behaviors like smoking, drinking, and drugs among the young. This study shows that not religion as such or internal religiosity, but largely observable (external) religiosity prevents them from wallowing in those vices. While this is found strongly for both males and females, those females doubting or reflecting religion show a somewhat smaller risky activity.
Keywords: I12; N34; Z12; 330; addictive behavior; Orthodox; external and internal religiosity; youth; smoking; drinking; drugs; Romania